Injectable high-strength hydrogel for bone tissue repair and preparation method thereof
Through the physical blending technology of linear temperature-sensitive polymers and functional fillers, an injectable hydrogel with high strength and multiple response characteristics was prepared, solving the problems of donor shortage, poor mechanical properties and surgical risks of bone repair materials. , achieving rapid filling of bone defects and new bone formation.
Patent Information
- Application Number
- CN202411668116.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Existing bone repair materials have problems such as shortage of donors, immune rejection, poor mechanical properties, fast biodegradation rate and risk of multiple surgeries, and injectable hydrogels lack filling and mechanical properties in complex spaces.
High-strength hydrogels are prepared by physical blending of linear temperature-sensitive polymers and functional fillers, and dehydration and strengthening are achieved in vivo using low critical dissolution temperature characteristics, combining bioactive glass particles to shorten the gelation time, enhance biocompatibility and Mechanical properties.
It achieves high-intensity, multiple response, biocompatible injectable hydrogels, which have good injectability and self-repairability, can quickly fill bone defects and promote new bone formation, reducing surgical risks.
Smart Images

Figure HDA0005145107950000011 
Figure HDA0005145107950000012 
Figure HDA0005145107950000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the cross-field of polymer materials and biomedical materials, and specifically relates to an injectable high-strength hydrogel for bone tissue repair and a preparation method thereof. Background Art
[0002] Bone defects caused by aging, trauma, tumors, etc. have a serious impact on human life. The most common treatment to solve this problem is autologous or allogeneic bone transplantation. More than 2 million bone transplants are performed worldwide each year. However, bone transplantation has problems such as donor shortage, immune rejection, and insufficient transplant materials. Therefore, alternative materials such as metals, bioceramics, and polymer hydrogels have been tried in the field of bone repair. Metal scaffolds can cause inflammation and allergic reactions, bioceramic scaffolds are non-degradable, and the processing conditions are harsh. Due to its three-dimensional porous network structure, polymer hydrogels can absorb a large amount of water or body fluids, are similar to the natural extracellular matrix (ECM) structure, are easy to deliver nutrients, and can load growth factors or bone cells. It has become an important candidate material in the field of bone tissue repair.
[0003] Natural polymers generally have good biocompatibility, but their mechanical properties and processability are mostly poor, and their biodegradation rate is too fast, which limits their application in the field of bone repair. In contrast, synthetic polymer hydrogels can be obtained through molecular and structural design to obtain multifunctional high-performance hydrogels, but synthetic polymers and their gels mostly have poor biocompatibility, which limits their application in tissue repair. In addition, hydrogel implantation into organisms usually requires secondary or multiple open surgeries. During the treatment process, repeated open surgeries increase medical risks and patient pain. Injectable hydrogels can use minimally invasive surgery to fill geometrically complex spaces, allowing the gel to be injected into irregular bone defects and reducing damage to surrounding tissues.
[0004] In view of the above problems, the present invention provides an injectable high-strength hydrogel for bone tissue repair. The polymer is copolymerized by hydrophilic structural unit hydroxyethyl acrylate and hydrophobic structural unit methyl acrylate, so that it has both groups that can form hydrogen bonds with water and groups that can coordinate with salt ions. By mixing in bioactive glass particles, the gelation time can be effectively shortened, and then according to the changes in the chemical and physical environment inside and outside the body, the phase change of the responsive polymer is used to achieve dehydration and strengthening of the gel before and after injection, so as to obtain a new injectable bone tissue repair hydrogel with multiple responses, good biocompatibility and high strength. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an injectable high-strength hydrogel for bone tissue repair and a preparation method thereof.
[0006] An injectable high-strength hydrogel for bone tissue repair comprises a linear thermosensitive polymer, a functional filler and a solvent. The mass ratio of the linear thermosensitive polymer to the solvent is 1:(1-9); the mass ratio of the functional filler to the linear thermosensitive polymer is 1:(2.33-19); wherein the linear thermosensitive polymer has an obvious lower critical solution temperature (LCST) in aqueous solution, and its LCST is adjustable within the range of 10-70°C; the linear thermosensitive polymer comprises a hydrophilic unit and an unsaturated hydrophobic unit; the molar ratio of the hydrophilic unit to the functional unit is 1:(0.1-9); the hydrophilic unit is selected from one or more of acrylamide, hydroxyethyl acrylate, N-vinyl pyrrolidone and acrylic acid; the unsaturated hydrophobic unit is selected from one or more of alkyl acrylate, alkyl methacrylate, N-alkyl acrylamide and polyoxyethylene alkyl acrylate, and the polymer is prepared by solution polymerization; the functional filler is selected from one or more of hydroxyapatite, bioactive glass and growth factor; the solvent is selected from one or more of pure water, ethanol and phosphate buffered saline.
[0007] The hydrogel absorbs water and swells at room temperature (25° C.), the modulus decreases, and the injectability is good. After the temperature reaches 37° C. after being injected into the body, the polymer hydrogel with LCST characteristics has enhanced water exudation and increased modulus.
[0008] The hydrogel has good injectability when containing a small amount of ethanol, and the strength of the gel increases as the ethanol is lost through metabolism in the body.
[0009] The present invention also provides a method for preparing the hydrogel:
[0010] The hydrogel is prepared by physical blending.
[0011] The preparation method of the hydrogel is carried out as follows: a hydrophilic monomer and an unsaturated hydrophobic monomer are dissolved in a solvent to prepare a solution with a monomer concentration of 5wt% to 30wt%, the initiation temperature is controlled at 10 to 80°C, an initiator is added after nitrogen is passed for deoxygenation to initiate polymerization for 3 to 8 hours to obtain a polymer solution; the polymer solution is transferred to a dialysis bag, deionized water is used for dialysis to remove small molecules whose molecular weight does not meet the preset requirements, and the supernatant is taken out and freeze-dried to obtain a copolymer; the copolymer is dissolved in water, and a functional filler is added thereto, and an injectable hydrogel is obtained after mixing. The hydrogel is obtained by shear thinning to obtain a hydrogel for bone defect repair.
[0012] The molar ratio of the unsaturated hydrophobic monomer to the hydrophilic monomer in the solution is 1:(0.25-9); the molecular weight distribution of the polymer is 2.1-10, and the molecular weight is 100,000-1,000,000; the content of the polymer is 10-50wt%; the content of the functional filler is 1-20wt%; the initiator can be any initiator well known to those skilled in the art, and there is no special limitation.
[0013] The invention also provides application of the hydrogel in the field of bone tissue repair.
[0014] The present invention has the following beneficial effects:
[0015] The invention provides an injectable high-strength hydrogel for bone tissue repair and a preparation method thereof. The high-strength hydrogel is obtained by physically blending a linear thermosensitive polymer, a functional filler and a solvent. The linear thermosensitive polymer has an obvious lower critical solution temperature (LCST) property in an aqueous solution, so that the hydrogel absorbs water and swells at low temperature and has good injectability. After being injected into the body, the temperature rises and the water exudation of the gel is enhanced. The hydrogel has the following beneficial effects: (1) The injectable hydrogel system of the present invention has good biocompatibility, mild reaction conditions, moderate reaction rate, no need to add small molecule cross-linking agents with bio / cytotoxicity, and low biotoxicity; (2) The hydrogel of the present invention has good shear thinning properties, and can be directly injected into the bone defect site through a medical syringe to achieve rapid filling of the bone defect, avoid secondary damage caused by surgery, and is easy to operate; (3) The hydrogel of the present invention has LCST in water or saline. By rationally designing the molecular structure and selecting suitable monomers and proportions, the hydrogel can absorb water and swell at 25°C (before injection) and has good injectability. At 37°C (after injection), the gel exudes water more strongly, providing good support for the damaged site; (4) The hydrogel of the present invention has a tendency to promote new bone formation without the addition of growth factors. After being mixed with functional fillers, it can effectively and quickly promote the repair of bone tissue. The functional fillers can form strong interactions with the polymer, which not only increases the cross-linking degree of the hydrogel network, but also improves the mechanical properties of the hydrogel, and is suitable for the repair of bone defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 1 is a scanning electron microscope image and an EDS mapping diagram of the injectable hydrogel obtained in Example 1 of the present invention, wherein Figure (a) is an electron microscope image of a pure hydrogel, Figure (b) is an electron microscope image of a hydrogel containing bioactive glass, Figure (c) is an electron microscope image of a hydrogel containing bioactive glass immersed in a PBS solution, and Figures (d) to (g) are EDS mapping diagrams of the sodium, calcium, silicon, and phosphorus elements at Figure (b);
[0017] Figure 21 is the rheological property test result of the injectable hydrogel obtained in Example 1 of the present invention, FIG. (a) is the viscosity change curve of the pure hydrogel with the shear rate, FIG. (b) is the viscosity change curve of the hydrogel with the shear rate after mixing with the bioactive glass, FIG. (c) is the viscosity change curve of the water / ethanol gel with the shear rate, and FIG. (d) is the viscosity change curve of the water / ethanol gel with the shear rate after mixing with the bioactive glass;
[0018] Figure 3 This is an experimental diagram of alternating large and small strain scanning of the injectable hydrogel obtained in Example 1 of the present invention;
[0019] Figure 4 This is the cytotoxicity result of the injectable hydrogel obtained in Example 1 of the present invention on rBMSCs cells;
[0020] Figure 5 1 is a general view of the specimen after the injectable hydrogel obtained in Example 1 of the present invention was injected into the rat skull, wherein Figure (a) is a blank group, Figure (b) is a pure hydrogel group, and Figure (c) is a group mixed with bioactive glass hydrogel;
[0021] Figure 6 These are Micro-CT scans and three-dimensional reconstruction images of the injectable hydrogel obtained in Example 1 of the present invention injected into the rat skull for 4 and 8 weeks. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The present invention provides an injectable high-strength hydrogel for bone tissue repair, which is obtained by physically blending a linear thermosensitive polymer, a functional filler and a solvent. The mass ratio of the linear thermosensitive polymer to the solvent is 1:(1-9); the mass ratio of the functional filler to the linear thermosensitive polymer is 1:(2.33-19); wherein the linear thermosensitive polymer has an obvious lower critical solution temperature (LCST) in an aqueous solution, and its LCST is adjustable within the range of 10-70°C.
[0024] The linear thermosensitive polymer comprises a hydrophilic unit and an unsaturated hydrophobic unit; wherein the molar ratio of the hydrophilic unit to the functional unit is 1:(0.1-9), preferably 1:(0.4-4), and most preferably 1:(1-3.5). The hydrophilic unit is selected from one or more of acrylamide, hydroxyethyl acrylate, N-vinyl pyrrolidone and acrylic acid, preferably hydroxyethyl acrylate and N-vinyl pyrrolidone, and most preferably hydroxyethyl acrylate. The unsaturated hydrophobic unit is selected from one or more of alkyl acrylate, alkyl methacrylate, N-alkyl acrylamide and polyoxyethylene alkyl acrylate, preferably alkyl acrylate and alkyl methacrylate, more preferably alkyl acrylate, and most preferably methyl acrylate. The linear thermosensitive polymer is prepared by solution polymerization.
[0025] The functional filler is selected from one or more of hydroxyapatite, bioactive glass and growth factors, preferably hydroxyapatite and bioactive glass, and most preferably bioactive glass.
[0026] The solvent is selected from one or more of pure water, ethanol and phosphate buffered saline solution.
[0027] The present invention provides an injectable high-strength hydrogel for bone tissue repair and a preparation method thereof, wherein a thermosensitive linear polymer is prepared using hydrophilic monomers and hydrophobic monomers as main raw materials, and then the polymer is dissolved in deionized water in a certain proportion to obtain an injectable hydrogel with shear-thinning properties; a certain proportion of functional fillers is mixed into the hydrogel to obtain an injectable hydrogel for bone tissue repair with controllable gelation rate and high strength. The shear-thinning injectable hydrogel of the present invention has good injectability, in vivo formability, biocompatibility and self-repairability, and has great application potential in the field of irregular bone lesion repair.
[0028] The preparation of the injectable hydrogel is carried out as follows: prepare a solution with a monomer concentration of 5wt% to 30wt%, control the initiation temperature at 10°C to 80°C, add an initiator to initiate polymerization for 3 to 8h after nitrogen gas is passed to deoxygenate, transfer the obtained polymer solution to a dialysis bag, dialyze with deionized water to remove small molecules, take out the supernatant and freeze-dry to obtain a polymer. Dissolve the polymer in deionized water, add a functional filler thereto, mix well to obtain an injectable hydrogel for bone tissue repair with shear thinning properties.
[0029] The monomers are hydroxyethyl acrylate and methyl acrylate, the functional filler is bioactive glass, and the initiator is any initiator well known to those skilled in the art without any special limitation.
[0030] The multi-responsive injectable hydrogel with bone defect repairing function of the present invention is further described below through examples.
[0031] The reagents used in the following examples are all commercially available.
[0032] Example 1
[0033] Methyl acrylate and hydroxyethyl acrylate are dissolved in N,N-dimethylformamide in a molar ratio of 1: (0.25-9), and a solution with a monomer concentration of 20wt% is prepared. The initiation temperature is controlled at 70°C, and after nitrogen is passed through to deoxygenate, the initiator azobisisobutyronitrile is added to initiate polymerization for 8 hours. The polymer solution is transferred to a dialysis bag with a molecular weight cutoff of 14,000, and dialyzed with deionized water for 5 days (small molecules with a molecular weight of less than 14,000 can be removed), and a poly (methyl acrylate-hydroxyethyl acrylate) copolymer is obtained after freeze drying. The above polymer is dissolved in deionized water to obtain injectable hydrogels with different water contents (50wt%-70wt%). Bioactive glass particles are dispersed in deionized water, and then the above polymer is added and mixed evenly to obtain an injectable hydrogel for bone tissue repair.
[0034] Example 2
[0035] The hydrogel obtained in Example 1 was freeze-dried and then brittle fractured, and the cross-sectional morphology of the hydrogel was observed using a scanning electron microscope, and the distribution of the bioactive glass in the gel was analyzed using an energy dispersive spectrometer. The acceleration voltage range of the scanning electron microscope was 0.2-30 kV+, and was continuously adjustable in 10V steps.
[0036] Figure 1 (a) to (c) are morphological images of the injectable hydrogel in Example 1 characterized by scanning electron microscopy. The results show that the hydrogel has a through-hole structure, which is conducive to the exchange of nutrients. Figure 1 (d) to (g) show the positional distribution of sodium, calcium, silicon, and phosphorus elements in the bioactive glass within the gel. The results show that the bioactive glass particles are mixed into the hydrogel and are evenly dispersed.
[0037] Example 3
[0038] The injectable hydrogel sample obtained in Example 1 was placed on the stage of the torque rheometer to examine the rheological behavior of the gel. The hydrogel sample was a disc with a thickness of 1 mm and a diameter of 8 mm. The edge of the gel was sealed with silicone oil to prevent water from evaporating during the test. In the injectable experiment, the test frequency was 1 Hz, the strain was 1%, the temperature was 25°C, and the shear rate test range was 0.1 s -1 Up to 1000s -1 In the self-healing experiment, the test frequency was 1 Hz, the temperature was 37°C, and alternating large and small strain scanning (large strain: 100%, small strain: 1%) was used.
[0039] Figure 2 and Figure 3 This is the rheological test result of the injectable hydrogel obtained in Example 1. Figure 2 As shown in the figure, at 25°C, the viscosity of the hydrogel decreases significantly with the increase of shear rate, showing obvious shear thinning characteristics, indicating that the hydrogel is injectable. Figure 3 As shown in the figure, at 37°C, the storage modulus (G′) of the hydrogel is always greater than the loss modulus (G″) regardless of whether it is under large or small strain, and the modulus is recoverable, indicating that the gel has self-healing properties.
[0040] Example 4
[0041] Mouse bone marrow mesenchymal stem cells (BMSCs) were selected to investigate the cell compatibility of the hydrogel obtained in Example 1 by live / dead cell staining. Live cells showing green fluorescence were observed under 490 nm excitation light, and dead cells showing red fluorescence were observed under 545 nm excitation light using a fluorescent inverted microscope, and the experimental results were recorded by taking photos.
[0042] Figure 4 The results of the cell compatibility test of the hydrogel obtained in Example 1 are shown in Figure 1. Green represents living cells and red represents dead cells. Figure 4 In (a), (b), and (c), a large number of living cells stained with Calcein-AM green can be seen, while only a few dead cells stained with red can be seen. Figure 4 As shown in (d), (e) and (f). Figure 4 (g), (h) and (i) are superimposed results of live and dead cell staining images, which can clearly compare the live / dead cell staining conditions. The above phenomenon shows that the injectable hydrogel of the present invention has good biocompatibility and is expected to be applied to bone tissue repair.
[0043] Example 5
[0044] The injectable hydrogel obtained in Example 1 was injected into the defective tissue of the rat skull, disinfected, and the experimental animals were routinely raised. The rats were euthanized after four weeks and eight weeks, respectively. The muscles and fascia of the rats were removed, the skull was retained, and it was placed in 4% paraformaldehyde for 24 hours and then transferred to new paraformaldehyde for fixation and placed for testing. Micro-CT was used to detect the repair of the defective skull of the rat. The test scanning parameters were: the scanning energy intensity was 70KVp, 114μA, the filter was 0.5Al, and the CT value was calibrated with 1200mg HA / ccm.
[0045] Figure 5 This is a gross specimen obtained in Example 1 4 weeks after the in vivo injection of the injectable hydrogel. Figure 6Micro-CT scanning and three-dimensional reconstruction were used to detect the generation of new bone tissue after the hydrogel was implanted in the body for 4 and 8 weeks. First, a scalpel was used to separate the skin fascia, expose the skull, and establish a defect model at the skull site. The hydrogel was injected into the defect site of the rat, and then the skin of the rat head was sutured and disinfected. The skull of the rats in the blank group was not treated. Observation of the CT images showed that new bone tissue was generated around the hydrogel 4 weeks after surgery, mainly distributed at both ends of the gel and the peripheral area. After 8 weeks after surgery, more new bone tissue was formed around the hydrogel, which had significant bone tissue repair ability compared to the blank group.
[0046] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An injectable high-strength hydrogel for bone tissue repair and a preparation method thereof, wherein the hydrogel comprises a linear thermosensitive polymer, a functional filler and a solvent; the mass ratio of the linear thermosensitive polymer to the solvent is 1:(1-9); the mass ratio of the functional filler to the linear thermosensitive polymer is 1:(2.33-19); wherein, The linear thermosensitive polymer has an obvious lower critical solution temperature (LCST) in aqueous solution, and its LCST is adjustable in the range of 10 to 70°C; the linear thermosensitive polymer includes a hydrophilic unit and an unsaturated hydrophobic unit; the molar ratio of the hydrophilic unit to the functional unit is 1:(0.1 to 9); the hydrophilic unit is selected from one or more of acrylamide, hydroxyethyl acrylate, N-vinyl pyrrolidone and acrylic acid; the unsaturated hydrophobic unit is selected from one or more of alkyl acrylate, alkyl methacrylate, N-alkyl acrylamide and polyoxyethylene alkyl acrylate, and the polymer is prepared by solution polymerization; the functional filler is selected from one or more of hydroxyapatite, bioactive glass and growth factor; the solvent is selected from one or more of pure water, ethanol and phosphate buffered saline.
2. The hydrogel according to claim 1, characterized in that The hydrogel absorbs water and swells at room temperature (25° C.), the modulus decreases, and the injectability is good. After the temperature reaches 37° C. after being injected into the body, the polymer hydrogel with LCST characteristics has enhanced water exudation and increased modulus.
3. The hydrogel according to claim 1, characterized in that The hydrogel has good injectability when containing a small amount of ethanol, and the strength of the gel increases as the ethanol is lost through metabolism in the body.
4. The hydrogel according to claim 1, characterized in that The preparation method of the hydrogel is physical blending, comprising the following steps: (1) dissolving a hydrophilic monomer and an unsaturated hydrophobic monomer in a solvent to prepare a solution with a monomer concentration of 5 wt% to 30 wt%, controlling the initiation temperature at 10 to 80° C., passing nitrogen to deoxygenate, and then adding an initiator to initiate polymerization for 3 to 8 hours to obtain a polymer solution; (2) transferring the polymer solution obtained in step (1) into a dialysis bag, dialyzing with deionized water to remove small molecules whose molecular weight does not meet the preset requirements, and taking out the supernatant and freeze-drying it to obtain a copolymer; (3) dissolving the copolymer obtained in step (2) in water, adding a functional filler thereto, and mixing well to obtain an injectable hydrogel, wherein the hydrogel is obtained through shear thinning to obtain a hydrogel for bone defect repair; Wherein, the molar ratio of the unsaturated hydrophobic monomer to the hydrophilic monomer in the solution of step (1) is 1: (0.25~9); The molecular weight distribution of the polymer in step (2) is 2.1 to 10, and the molecular weight is 100,000 to 1,000,000; The content of the polymer in step (3) is 10 to 50 wt %; the content of the functional filler is 1 to 20 wt %.
5. Use of the hydrogel according to any one of claims 1 to 4 in the field of bone tissue repair.
Citation Information
Patent Citations
Use of gel material in therapeutic process of dental disease
CN103006444A
Preparation method and device of temperature-sensitive gradient injectable hydrogel
CN113750915A
Reverse temperature-sensitive copolymer and preparation method thereof
CN114478891A
Cited By
3D printing high-strength supramolecular hydrogel and application thereof in bone defect repair
CN121059891A